Islamic banking : adoption of a service innovation. - Mohd Yusri Reki B Yusof. (2010)
Past literature revealed a lack of marketing studies on Islamic banking. A consumerbased research study was thus considered to be beneficial for both academicians and practitioners. The present study applied the diffusion model of Rogers (1983) in the context of introducing Islamic banking to the Muslim community in Singapore. For the purpose of this study, a proportion of the sample consisted of members of the Association of Muslim Professionals (AMP). Professionals are regarded important because of their tendency to be more receptive towards innovations their ability to significantly influence others to adopt (Rogers 1983). Sampling was also carried out at by getting responses from three local mosques and their responses were used for comparative purposes with the AMP responses.